Implementación y evaluación del aplicativo móvil para el manejo adecuado de las técnicas manuales de instrumentación en endodoncia (2023)
There are a variety of applications oriented to teaching-learning for health students, which facilitate learning. Thanks to this, a range of possibilities is obtained in the field of health and in the training of professionals in this area.